Beyond Informality: Housing Quality and Tenure Insecurity in Tanzania’s Secondary Cities - Asia Khamis Nyange (Muslim Business and Economics Review, 2026)
Sub-Saharan Africa is experiencing high rates of urbanisation that have driven the housing deprivation problem into dense informal settlements, but the link between tenure status and housing quality is yet to be fully examined in secondary cities in Tanzania. This study examines the impact of tenure on housing quality and examines whether household wealth, education, and migration status mediate the relationship between tenure and housing quality. The analytical sample consists of 2,411 households from the Tanzania National Panel Survey (NPS) Wave 5 (2020–2022) in secondary cities. A standardised Housing Quality Index (HQI) was built using the seven structural and service indicators and ordinary least squares regression with cluster-robust standard errors and interaction terms. The results show that there is a significant difference between informal and formal owners in terms of the reduction in HQI (β = −0.42, p = 0.003), which supports the tenure penalty hypothesis. On the other hand, the housing quality of households in other tenure arrangements (employer-provided or free accommodation) shows a significant positive value (β = +0.25, p = 0.027). Wealth and education have independent positive effects on housing quality, but there are interaction effects between wealth and informal tenure (β = 0.286, p = 0.008), and between education and informal tenure (β = 0.036, p = 0.058). Migration status does not have any significant interaction effects. Robustness checks (Ramsey RESET test, Cook's distance, and VIFs) validate the model and confirm its reliability. The study concludes that tenure insecurity is a 'structural constraint' not easily mitigated by household resources, and calls for enhancing informal tenure recognition, increasing hybrid housing forms, and including the poor in terms of their wealth in informal housing in policy agendas at the secondary city level.